A Broadband Filter Transmitarray Based on Quasi-Yagi Antenna Element. (September 2020) - Sun, Fugang; Li, Chuanqing; Liu, Yi; Wan, Lulan; Qin, Fan; Liu, Yi
Abstract: A transmitarray (TA) antenna operating at X-band with band-pass filtering performance is presented. The proposed antenna is composed of a wideband TA and a filter feed antenna. Two quasi-Yagi antennas are connected as the unit cell of the proposed TA, leading to high transmission efficiency over a broadband range. By simply changing the length of the transmission lines, 360° phase shift is obtained. To verify this idea, a design with 16×26-unit cells is simulated and optimized, showing that approximately 14.5% 1-dB and 24.6% 3-dB gain bandwidths are achieved, respectively, with the peak gain of 23.1 dBi. Moreover, by employing the bandpass filter feed antenna, good bandpass filtering property is achieved, showing that the upper and lower out-of-band suppression in the 0.3GHz range can reach 27.3dB and 24.2dB, respectively, with the passband range from 9.6GHz to 11.9GHz.